1979
DOI: 10.1007/bf00390238
|View full text |Cite
|
Sign up to set email alerts
|

The genetic hypothesis for susceptibility to lepromatous leprosy

Abstract: Evidence for genetic influence of the host response to infection with Mycobacterium leprae is reviewed. A complex segregation analysis is performed on data for 91 families from Mactan, Philippines, in each of which at least one offspring developed lepromatous leprosy. The data are not found to be inconsistent with an autosomal recessive hypothesis for susceptibility to lepromatous leprosy. Heritability estimates in the range of 80% were calculated for sib-sib pairs under the multifactorial hypothesis for susce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

1982
1982
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 34 publications
0
11
0
2
Order By: Relevance
“…More recent studies have considered clinical status of leprosy in family members as well as age-of-onset effects. Smith (1979), in a complex segregation analysis of Filipino families in which at least one male offspring had lepromatous leprosy, found di.stributions consistent with autosomal recessive inheritance of susceptibility to lepromatous leprosy but argued in favor of a multifactorial hypothesis with heritability of about 80%. This illustrates a difficulty in human genetics methodology that has been noted by many authors (Reich etal.…”
Section: Pedigree Analysismentioning
confidence: 99%
“…More recent studies have considered clinical status of leprosy in family members as well as age-of-onset effects. Smith (1979), in a complex segregation analysis of Filipino families in which at least one male offspring had lepromatous leprosy, found di.stributions consistent with autosomal recessive inheritance of susceptibility to lepromatous leprosy but argued in favor of a multifactorial hypothesis with heritability of about 80%. This illustrates a difficulty in human genetics methodology that has been noted by many authors (Reich etal.…”
Section: Pedigree Analysismentioning
confidence: 99%
“…The roles of hereditary and environmental factors in the determination of the occurrence and types of leprosy have long been debated. Among voluminous amounts of literature, the recent publication on segregation analysis by Smith [14] and the study on twins by Chakravartti and Vogel [l] clearly demonstrated the relative importance of the hereditary factors in the occurrence of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…A number of segregation studies have been carried out for leprosy (1,3,84,117,171,241,275,280,289,327), several of which have detected the presence of a recessive or codominant mode of inheritance for leprosy overall or for nonlepromatous leprosy (1,84,117,171,289).…”
Section: Assessing the Genetic Contribution To Leprosy Riskmentioning
confidence: 99%